(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
The article analyzes the administrativeization of tax policy in Uzbekistan, Kashkadarya region, in 1925–1929 and its impact on the collectivization process. The management of this process has shifted from a stable incentive to a new administrative economic structure to one of control and class pressure. The example of Kashkadarya highlights the process of developing tax plans, financial application of financial bodies at the regional level, to the population, and the reorganization of agriculture through land and water reform